OP0340 Evidence based recommendations for corticosteroid tapering/discontinuation in new onset juvenile dermatomyositis patients from the printo trial. (12th June 2018) - Giancane, G.; Lavarello, C.; Pistorio, A.; Zulian, F.; Magnusson, B.; Avcin, T.; Corona, F.; Gerloni, V.; Pastore, S.; Marini, R.; Martino, S.; Pagnier, A.; et al.
Abstract : Background: At present no clear evidence based guidelines exist to standardise the tapering and discontinuation of corticosteroids (CS) in juvenile dermatomyositis (JDM). Objectives: To provide evidence-based recommendations for CS tapering/discontinuation through the analysis of the patients in the PRINTO new onset JDM trial. Secondary objective of the study was to identify predictors of clinical remission and CS discontinuation. Methods: New onset JDM children were randomised to receive either prednisone (PDN) alone or in combination with MTX or CSA. All children were given initially intravenous methylprednisolone, and then PDN starting with 2 mg/kg/day. Gradual tapering according to a specific protocol could lead to the safe dose of 0.2 mg/kg/day by month 6, then discontinued at month 24. Major therapeutic changes (MTC) were defined as the addition or major increase in the dose of MTX/CSA/other drugs or any other reasons for which patients were dropped from the trial. Patients were divided according to clinical remission (CR) (CMAS=52 and MD global=0 for 6 continuous months) into two major groups. Group 1 included those on CR, who could discontinue PDN, with no MTC (reference group). Group 1 was compared with those who did not achieve CR, without or with MTC (group 2 and 3, respectively). JDM core set measures (CSM) were compared within the 3 groups. We also calculated the gold standard group 1 median change in the CSM in the first 6 and over 24 months and applied a logistic regression model to identify predictors of CR with PDN discontinuation. Results: 139 children were enrolled in the trial: 47 on PDN, 46 on PDN +CSA and 46 on PDN +MTX. We identified 30 (21.6%) patients for group 1, 43 (30.9%) for group 2 and 66 (47.5%) for group 3. At baseline all 3 groups had no differences in the CSM. Already in the first 2 months a clear differential trend in disease activity measures, according to clinical remission status and PDN discontinuation, could be identified. From the observation of the median change in the CSM of group 1 in the first 6 months, the following recommendations could be extrapolated: decrease corticosteroids from 2 to 1 mg/kg/day in 2 months if the MD-global, parent-global, CHAQ, DAS, CMAS, MMT or Phs measures have changed of at least 50%; from 1 to 0.5 mg/kg/day in the following 2 months if the MD-global, CHAQ, DAS, CMAS show a change of at least 20%; in the following 2 months (month 4–6) corticosteroids can be tapered up to the safe dose of 0.2 mg/kg/day, if the disease activity measures remain at low/normal values. We finally ran a logistic regression model that showed that the achievement of PRINTO criteria 50–70–90 at 2 months from disease onset, an age at onset >9 years and the combination therapy PDN +MTX, increase the probability of clinical remission from 4 to 7 times (table 1). Conclusions: We propose evidence based specific cut-offs for corticosteroid tapering/discontinuation based on the change in JDM CSM of disease activity, and to identify the best predictors for clinical remission and corticosteroid discontinuation. Disclosure of Interest: None declared